Rekonstruksi Konsep Eudaimonia dan Phronesis Aristoteles dalam Pengembangan Pendidikan Karakter Kontemporer - Laurentius Tinambunan; Sergius Lay; Largus Nadeak; Antonius P Sipahutar; Martina Rosmaulina Marbun; Fitra Zebua (Coram Mundo: Jurnal Teologi dan Pendidikan Agama Kristen, 2026)
This research reconstructs the concept of the ideal human being in Aristotelian philosophy and formulates its implications for contemporary character education. The study is grounded in modern educational challenges that require not only intellectual mastery but also the cultivation of complete character based on virtue. Using library research with a hermeneutic approach, this study critically interprets Aristotle’s key concepts, particularly eudaimonia, phronesis, and virtue ethics, and contextualizes them within current educational needs. Data were collected from relevant primary and secondary literature and analyzed through thematic and conceptual analysis to identify the relationship between Aristotelian ideas and character education. The findings show that the ideal human being, according to Aristotle, is one who achieves eudaimonia through the balanced development of moral and intellectual virtues, guided by phronesis as practical wisdom. Education is therefore understood as a gradual process of character formation through habituation, experience, role modeling, reflection, and ethical deliberation. This study proposes five strategies for Aristotelian character education: virtue habituation, experiential learning, educator role modeling, ethical deliberation, and context-based integral education. The study contributes a virtue-based educational model that emphasizes wisdom, responsibility, virtue, and the realization of the good life within society.